2015
DOI: 10.1378/chest.14-2457
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Profiles in Asthma With High vs Low Airway Reversibility and Poor Disease Control

Abstract: BACKGROUND: High bronchodilator reversibility in adult asthma is associated with distinct clinical characteristics. Th is analysis compares lung function, biomarker profi les, and disease control in patients with high reversibility (HR) and low reversibility (LR) asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 9 publications
5
44
1
Order By: Relevance
“…We did not observe an association to FE NO levels, a marker easily suppressed by compliance with ICS therapy. This is in contrast to a smaller study by Kupczyk and coworkers (9) showing a link between EPA status and elevated FE NO levels, but consistent with a larger retrospective biomarker analysis of two recent clinical trials (28). Additionally, adults in the SARP-3 cohort seem to have an inverse relationship between exacerbations and IgE levels ( Figure 3) or degree of allergen polysensitization (Table 3, Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We did not observe an association to FE NO levels, a marker easily suppressed by compliance with ICS therapy. This is in contrast to a smaller study by Kupczyk and coworkers (9) showing a link between EPA status and elevated FE NO levels, but consistent with a larger retrospective biomarker analysis of two recent clinical trials (28). Additionally, adults in the SARP-3 cohort seem to have an inverse relationship between exacerbations and IgE levels ( Figure 3) or degree of allergen polysensitization (Table 3, Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies have shown a lack of association between IgE levels and measures of asthma control, and lower levels of IgE in patients with poor bronchodilator responsiveness (15,28). Collectively, although patients with high levels of type 2 inflammatory biomarkers are at increased risk of exacerbation, those with frequent exacerbation may or may not have high levels of type 2 inflammation at the time of assessment.…”
Section: Number Of Exacerbations In the Lastmentioning
confidence: 99%
“…This finding is in contrast to a previous review, which found a higher rate of atopic conditions such as sinusitis in patients with uncontrolled asthma, albeit in an elderly population (36). Conversely, T helper 2 inflammation, which is associated with uncontrolled asthma, has been observed independent of atopic status in some SA populations (37,38). These previous findings support the possibility that, in this population of patients with SA, atopic conditions such as eczema and sinusitis may not have increased in prevalence with uncontrolled disease, but were associated with a lower risk of uncontrolled disease.…”
Section: Discussioncontrasting
confidence: 96%
“…Bronchodilator response has been reported to inversely correlate with the degree of hyperresonsiveness to adenosine 5 0monophosphate (AMP) during bronchial challenge [11], which is known to reflect the persistence of underlying bronchial inflammation in asthma [12]. Moreover, there is evidence of correlation between bronchodilator response and other markers of airway inflammation such as exhaled nitric oxide [13,14], eosinophils in bronchial biopsy specimens [15] or a combination of serum IgE, blood eosinophils and exhaled nitric oxide [16].…”
Section: Patients With Airway Obstruction (N ¼ 76)mentioning
confidence: 99%